Dora's chilly day - Thorpe, Kiki.; Savitsky, Steven (New York : Simon Spotlight/Nick Jr., 2007)
Dora and her friend, Boots the monkey, must cross the Troll Bridge and go through the Nutty Forest to reach the Chocolate Tree and bring some chocolate home for Dora's grandmother to make a special chilly day treat.
"Based on the TV series Dora the Explorer as seen on Nick Jr."--T.p. verso.
"Spotlight"--T.p. verso.
1.9
K-3
Text mainly in English with some Spanish words.
Keywords: Cold -- Juvenile fiction; Dora the Explorer (Fictitious character) -- Juvenile fiction; Explorers -- Juvenile fiction; Girls -- Juvenile fiction; Weather -- Juvenile fiction; Adventure and adventurers -- Fiction; Cold -- Fiction; Dora the Explorer (Fictitious character) -- Fiction; Explorers -- Fiction; Girls -- Fiction; Weather -- Fiction; Adventure fiction; Cold -- Fiction; Dora the Explorer (Fictional character) -- Fiction; Explorers -- Fiction; Girls -- Fiction; Weather -- Fiction; Adventure fiction; Picture books for children